AB1346 The clinical course of patients with biologics-treated rheumatoid arthritiscomplicated with nontuberculous mycobacterial lung infection. (12th June 2018) - Kise, T.; Shimada, K.; Miyoshi, Y.; Yokogawa, N.; Sugii, S.
Abstract : Background: For now, it has been difficult for rheumatoid arthritis (RA) patients with lung nontuberculous mycobacterial infection (LNTMI) to achieve therapeutic goal of RA because of insufficient treatment considering the risk of NTM deterioration by immunosuppressive therapy. Although use of biologics in RA with LNTMI is not recommended based on results of an epidemiological study from USA, 1 2 prognosis analysis considering confounding factors, including the species of NTM, remains to be studied. On the other hand, some Japanese case series of RA with LNTMI after biological treatment had shown the acceptable outcomes. 3 Objectives: This study was performed in order to investigate clinical course of patients with biologics-treated RA complicated with LNTMI. Methods: This study is descriptive study. All the patients diagnosed with RA and proved the positivity of acid fasting culture were extracted. We retrospectively collected the clinical data between 1 Jan 2011 and 31, Mar 2017 including age, sex, date of RA onset, onset of NTM infection, species of NTM organisms, biologic drugs used, the clinical course, the findings of high resolution computed tomography (HRCT) and the outcome after commencement of biologics, at Tokyo Metropolitan Tama Medical Centre. The diagnosis of LNTMI was made by satisfying both of the two following conditions; 1 either positivity of bronchoalveolar lavage fluid culture at least once or sputum culture twice or more and 2 the compatible findings with LNTMI on HRCT. Results: During investigation period, 13 LNTMI-RA patients were administered biologics, of which 76.9% were female. Their mean age at NTM diagnosis was 71 years old. The duration between the RA diagnosis and the occurrence of LNTMI ranged widely from 1 to 40 years. The species of NTM were Mycobacterium. avium (12 cases) and M. intracellulare (1 case), which did not include rapid growing species. Twelve cases had treated with glucocorticoid. Of 10 cases who underwent biologics therapy after NTM diagnosis, 6 had continued biologics after diagnosis of LNTMI. All the 4 of the 13 cases who first received biologics after diagnosis of LNTMI were treated with abatacept, which improved their RA activity and did not exacerbate LNTMI. Of the 13, there were no patients requiring home oxygen therapy. During the average observational period after LNTMI of 3.6 years (0.8–10.3 years), 10 of the 13 were alive and 3 died, whose causes of death were not directly associated with LNTMI. When each period upon every biologics was independently calculated, the Kaplan-Meier survival curve illustrated the tendency of survival difference of between LNTMI-RA cases treated with non-TNF inhibitors and those with TNF inhibitors (figure 1). Conclusions: Even when patients with RA have LNTMI of not rapid growing species, RA may be safely and sufficiently treated by abatacept with careful monitoring of the respiratory condition, which may improve their joint prognosis. References: [1] Winthrop KL, et al. Emerg Infect Dis. 2009;15(10):1556–61. [2] Winthrop KL, et al. Ann Rheum Dis. 2013;72(1):37–42. [3] Mori S, et al. Mod Rheumatol. 2012;22(5):727–37. Disclosure of Interest: None declared